Perovskitas óxidas para aplicação eletroquímica e fotovoltaica - Dias, Jeferson Almeida (2019)
This work aimed to investigate the production of lanthanum perovskites LaCoO3 and LaFeO3 in the form of thin films and to evaluate their use as catalysts for water splitting as well as absorbers for photovoltaic devices. That is, focusing on renewable energy. For such, the conventional polymeric precursor method was applied in the deposition of films, being improved with different polymer modifiers (amphiphilic copolymer Pluronic P123 and polyethylene glycol) – aiming to produce oxide films with greater homogeneity and enhanced morphological properties. Particularly, the combination of the polymeric precursor method and the amphiphilic copolymer Pluronic P123 is new in the literature for thin films deposition and is the greatest novelty of this work. Results demonstrated that the traditional polymeric precursor method was efficient in perovskite production with promising electrocatalytic activity. However, the produced films lacked homogeneity. On the other hand, the amphiphilic copolymer and resin combination allowed more effective spreading over the substrate. Therefore, films that are much more homogeneous, reproducible and with lower level of defects were obtained. The polyethylene glycol altered film rugosity, enhancing its catalytic activity. The photovoltaic devices built, in specific configurations, proved to be photosensitive – confirming the potentiality of the studied oxide perovskites for optoelectronic applications. Hence, results indicated that the lanthanum-based oxide perovskites are favorable for these applications and can be produced quite simply in the form of thin films using deposition strategies by solution improved in this study.